Pemakzulan Presiden/Wakil Presiden Menurut Undang-Undang Dasar 1945 - M. Laica Marzuki (Jurnal Konstitusi, 2010)
Article 6A (1) of 1945 Constitution  regulated  that  the  President and the Vice President of the Republic elected as a pair by direct voting from all citizen. Based on this rule, the position of the President and Vice President is quite powerful, thus almost impossible to be impeached during their term. Prior to the Constitutional Amendment, there is no constitutional article that regulates on the issues and mechanism of Presidential Impeachment. The Third Amendment, which adopted at the 7th Plenary Meeting of the Peoples Consultative Assembly (MPR), November 9th 2001, regulates on the mechanism of Presidential impeachment in the Article 7A which stated, The President and/or Vice President may be dismissed from office by the MPR based on a proposal from the DPR, either when proven guilty of violating the law by betrayal of the state, of corruption, of bribery, of any other felony, or because of disgraceful behaviour, as well as when proven no longer to fulfil the conditions as President and/or Vice  President.